Dividend yields and stock returns: Implications of abnormal January returns - Keim, D (Journal of Financial Economics, 1985)
This study examines the empirical relation between stock returns and (long-run) dividend yields. The findings show that much of the phenomenon is due to a nonlinear relation between dividend yields and returns in January. Regression coefficients on dividend yields, which some models predict should be non-zero due to differential taxation of dividends and capital gains, exhibit a significant January seasonal, even when controlling for size. This finding is significant since there are no provisions in the after-tax asset pricing models that predict the tax differential is more important in January than in other months.